MP27: Costs of emergency syncope care in Canada. (15th May 2017) - Kim, S.; Cook, O.; Yau, L.; Mukarram, M.A.; Arcot, K.; Ishimwe, A.; Thavorn, K.; Taljaard, M.; Sivilotti, M.; Rowe, B.H.; Thiruganasambandamoorthy, V.
Abstract : Introduction: Syncope is a common emergency department (ED) presentation and constitutes 1% of all ED visits, approximately 160, 000 visits annually across Canada. Lack of standardized syncope care has economic and cost implications. Currently, emergency medical services (EMS) is over utilized, variations in ED management exist and a substantial proportion (46.5%) are hospitalized for cardiac monitoring. Our previous studies have proposed ways to reduce health care utilization through development of EMS clinical decision tool, ED risk scores and remote cardiac monitoring. We sought to: 1) Estimate costs associated with syncope care in the pre-hospital, ED and inpatient settings; and 2) Determine potential cost savings if the proposed alternate strategies were adopted.Methods: A prospective cohort study was conducted in five Canadian EDs from 2010-2014. We enrolled adult (≥16 years) syncope patients and excluded those with prolonged loss of consciousness, mental status changes, seizure, significant trauma, or alcohol/illicit drug abuse. Demographics, medical history, mode of arrival, EMS time points, reasons for hospitalization, ED and inpatient length of stay, final ED diagnosis and any serious adverse event within 30 days of index visit were collected. Descriptive and inferential statistics were used.Results: Out of 4, 064 patients enrolled, 67.3% were transported to the ED by EMS and the average cost per event was 262.78 (range at study sites: 156.43-553.03). The average cost per ED visit was 267.98 (range: 174.66-374.95). 12.9% of the patients were admitted and the average of cost per admission was 9, 886.15 (range: 9, 715.23-10, 277.98). Syncope is associated with an estimated total annual cost of 257 million. In Canada, we estimate that diverting low-risk patients will save 5 million in the pre-hospital setting and 15 million in the ED annually, and implementing a remote cardiac monitoring strategy will save 50 million annually.Conclusion: It is estimated that the proposed strategies will save 70 million annually. This is likely an underestimation as cost savings due to reduction in investigations related to diversion of ED patients, reduction in ED length of stay and hospitalization are unaccounted. Adoption of similar strategies will likely lead to significantly higher cost savings in countries with higher resource utilization for syncope management.